The relationship of high performance work systems on turnover intention in Chinese companies - Li Yixian (2020)
Most companies in China are gradually focus on implementing high performance work systems (HPWS) to enhance the organizational performance and productivity. These practices are accepted to be universally effective into retaining employees but in fact their nature is targeting motivations that are not homogeneous across age and life stages. The opportunity to explore the differential effectiveness of HPWS is a research gap that deserves attention. This study seeks to analyze the impact of HPWS on employee retention testing for the moderation effect of employee age. With a sample of 236 workers from several industries in China, findings show HPWS are more effective in the younger working population in China when compared to the older one. Findings are discussed at the light of theory and implications for HRM explored.